A consciência metacognitiva em médicos residentes em oftalmologia - Lessa, Phillype Fernandes (2024)
The importance of medical professionals in human life has led to a growing interest in incorporating aspects of various natures into their training stage, including metacognitive aspects. In the case of medical residency training, it is important that these professionals, once imbued with their academic-scientific knowledge, can focus their attention on the field of specific professional practice. At the same time, they need to continue learning and making decisions based on an autonomous and conscious process, elements that are the essence of metacognitive thinking. In this context, metacognition emerges as a form of thinking that can help resident physicians structure their actions based on awareness of their own knowledge and the ability to control their executive actions, in order to achieve success in their activity. The training of ophthalmologists, as it is linked to metacognitive processes, is accompanied by awareness of their lived experiences in the form of judgment, feelings and emotions in the face of what is presented, that is, the clinical cases they have to deal with on a daily basis. Based on these considerations, the present study infers the following research question: what metacognitive manifestations are identified in the speech of resident physicians when asked about their activities during medical residency? The objective is to analyze the presence of metacognitive manifestations in resident physicians in ophthalmology when they talk about their training and professional performance during medical residency. To achieve the proposed objective and answer the research question, a qualitative investigation of the case study type is carried out, supported by the use of semi-structured interviews. The study participants are six resident physicians in ophthalmology at a hospital located in the northern region of Rio Grande do Sul. The data produced are analyzed in light of the understanding of metacognition and the specificities of a training process carried out during the medical residency period. After being transcribed and read, the data are examined based on two categories given a priori, in order to seek answers to the research question, namely: (a) metacognitive manifestations of resident physicians associated with metacognitive components; (b) metacognitive awareness of resident physicians about the training period of the medical residency. The results indicate that, in the case of the first category, it is clear that there is a significant difference between the participants, revealing that some externalize metacognitive manifestations more clearly, describing a path and choices that lead them to make choices and decisions more effectively. In the case of the second category, the results indicate that, when faced with the decision to become a doctor or even to undertake a residency in ophthalmology, metacognitive thinking is rarely present. However, when a set of hypothetical situations involving this specific residency were proposed, three of the participants demonstrated activation of this form of thinking, which shows that, at times, it may be present in the doctor's actions, but is only difficult for him to externalize. Finally, the study highlights the importance of its continuity as a way of observing the performance of this professional and, thus, establishing data that allow for a broader analysis of the presence of metacognitive thinking in the actions of resident doctors.